A novel murine PKA-related protein kinase involved in neuronal differentiation - Blaschke, Rüdiger Jörg; Monaghan, A. Paula; Bock, Dagmar; Rappold, Gudrun (Genomics, 2000)
Members of the cAMP-dependent second-messenger pathway have been described as regulators of cellular growth and differentiation and were consequently implicated in a variety of embryogenic processes including brain development. Moreover, recent data suggest an indispensable role for cAMP-dependent protein kinases (PKAs) in neuronal differentiation and synaptic plasticity. Using a degenerate primer-based approach, we have identified a novel murine gene closely related to the human cAMP-dependent protein kinase PRKX on Xp22.3. This gene (Pkare) was mapped to the region near the centromere of the murine X chromosome and is expressed in a variety of adult organs including kidney, liver, spleen, testis, ovary, lung, heart, and brain. Antisense in situ hybridization on staged mouse embryos revealed a highly distinctive expression pattern during neuronal development, with elevated Pkare expression observed only in differentiating neurons within the first ganglion, the dorsal root ganglia, and the mantle layer of the telencephalon. Based on the close relationship with the catalytic PKA subunits and its distinct expression in differentiating neuronal cells, Pkare might represent a novel component of the cAMP-regulated pathways involved in brain development and function.
Gesehen am 25.03.2021